Los simuladores virtuales en el aprendizaje de Ciencias Naturales de los estudiantes del cuarto año de educación general básica de la “Unidad Educativa Riobamba” Periodo Lectivo 2021-2022 - Logroño Parra, Lissett Andreina (2024)
The research work presented with the title: "Virtual simulators in the learning of Natural Sciences of the students of the fourth year of Basic General Education of the "Unidad Educativa Riobamba" school period 2021-2022", is an important topic since The technologies and the strong repercussions in the educational field in a digital and globalized world bring with them the need to make changes in the teaching practice, an inquiry that had as its primary objective: To determine the use of interactive virtual simulators for the learning of Natural Sciences, allowing students to have a more significant relationship with the contents and their knowledge to be autonomous, typical of their lived experiences. The research design, under a mixed approach, combines elements of qualitative and quantitative research in order to determine the virtual simulators in learning the area of Natural Sciences; The type of research used was exploratory, descriptive, with a research method: inductive, deductive and hermeneutic. We worked with a sample of 35 students between boys and girls in the fourth year of EGB and 3 teachers from the Natural Sciences area. For the collection of information, the survey was used as a technique; As instruments were used: a questionnaire, which was applied to the fourth year students of EGB and an interview with the teachers of the Educational Unit, instruments that were used with the purpose of obtaining the necessary information about the problem. Coming to the conclusion that educational simulators are adequate to strengthen the knowledge of students, which is why a guide to virtual simulators in the area of Natural Sciences is proposed, which facilitates its educational use for both students and teachers.